Signaling cascades in thyroid cancer: Increasing the armory of archers to hit bullseye. Issue 5 (22nd January 2018) - Rashid, Faiza Abdul; Mansoor, Qaisar; Tabassum, Sobia; Aziz, Hafsa; Arfat, Waleed O.; Naoum, George E.; Ismail, Muhammad; Farooqi, Ammad Ahmad
Abstract: Thyroid cancer is a multifaceted and therapeutically challenging disease and rapidly accumulating experimentally verified findings have considerably improve our understanding of the molecular mechanisms which underlie its development. Substantial fraction of information has been added into existing landscape of molecular oncology and we have started to develop a sharper understanding of the underlying mechanisms of thyroid cancer. Wealth of information demystified different intracellular signaling cascades which are frequently deregulated in thyroid cancer. In vitro assays and xenografted mice based studies have helped us to identify drug targets and different synthetic and natural products are currently being tested to effectively treat thyroid cancer. Cabozantinib and vandetanib have been approved to treat medullary thyroid cancer (MTC) and two agents (lenvatinib and sorafenib) are also being used to treat radioactive‐iodine refractory differentiated thyroid cancer. This review comprehensively summarizes most recent advancements in our knowledge related to dysregulated intracellular signaling cascades in thyroid cancer and how different proteins can be therapeutically exploited. (1) We discuss how loss of TRAIL mediated apoptosis occurred in thyroid cancer cells and how different strategies can be used to restore apoptosis in resistant cancer cells; (2) We provide detailed account of seemingly opposite roles of NOTCH signaling in thyroid cancers; (3) TGF/SMAD mediated signaling also needs detailed research because of context dependent role in thyroid cancer. Researchers have only begun to scratch the surface of how TGF signaling works in thyroid cancer and metastasis; and (4) Role of SHH signaling in thyroid cancer stem cells is also well appreciated and targeting of SHH pathway will be an important aspect in treatment of thyroid cancer. Better concepts and improved knowledge will be helpful for clinicians in getting a step closer to individualized medicine. Abstract : Thyroid cancer is a multifaceted and therapeutically challenging disease and rapidly accumulating experimentally verified findings have considerably improve our understanding of the molecular mechanisms which underlie its development. Substantial fraction of information has been added into existing landscape of molecular oncology and we have started to develop a sharper understanding of the underlying mechanisms of thyroid cancer. Better concepts and improved knowledge will be helpful for clinicians in getting a step closer to individualized medicine.